Kepuasan Pelanggan Internal Terhadap Kualitas Pelayanan Unit Rekam Medis RSU X - Annisa Puji Astuti; Andi Suhenda (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
The quality of service received by customers is one of the determinants of aspects of customer satisfaction, including internal customers. Measuring internal customer satisfaction with the quality of service of the medical record unit has never been carried out, and based on the results of a preliminary study 3 out of 4 internal customers are dissatisfied with the quality of service in the medical record unit. The aim of the study was to describe internal customer satisfaction with service quality at the medical record unit of RSU “X”. This type of descriptive quantitative research. Total population is 728, sample is 88 respondents, proportionate stratified random technique. Data collection by distributing questionnaires, data analysis using univariate analysis. The results of the study were in the form of the highest percentage of respondents' characteristics, namely female sex (63.6%), age group 26-35 (38.6%), last education diploma (54.5%), and nursing profession (70.5%). Frequency distribution of responsiveness dimensions (63.6%), reliability dimensions (78.4%), assurance dimensions (92.0%), empathy dimensions (76.1%), and physical evidence dimensions (86.4%). Overall, the satisfaction category was obtained (64.8%). Internal customer satisfaction with the service quality of the medical record unit based on the quality dimension and overall the respondents were satisfied.